All our Authors: Open Access Publishing Agreements and Academic Research Library Websites in the United States - Gene R. Springs (027.7)
Since 2018, open access publishing agreements continue to accelerate in the United States among academic research libraries and their consortia as the global scholarly publishing marketplace shifts, adapts, and transforms to address myriad open access mandates and policies from around the world. In the United States, the White House’s Office of Science and Technology Policy (OSTP) August 2022 memorandum mandating public access to federally funded research with an implementation deadline of December 31, 2025 is further accelerating this shift as researchers, funders, and publishers work to understand requirements. As different open access publishing models, including Transformative Agreements, pure publish agreements, and Subscribe 2 Open are introduced, piloted, and entered into, academic research libraries must identify approaches to communicate to their campus authors details and information about the various agreements in which they participate on behalf of their universities.This paper examines if and how academic research libraries in the United States present information on their websites to communicate details about open access publishing agreements to their constituents including the following questions: where is this information available? What kind of agreements are listed? Alongside what other resources are these details presented? Are outreach and education opportunities promoted? What kind of contact information is listed for support and help? Understanding how academic research libraries are currently communicating information about these agreements can help to inform future strategies around outreach to researcher authors as well as educational opportunities for librarians in our organizations as content agreements are married with open access publishing benefits.